An Analysis of Early Reading Difficulties at First-Grade Students: A Case Study at MI Negeri 2 Jember - M. Adin Ferdiansyah; Khusnaliyah, Khusnaliyah (Pascasarjana UIN Kiai Haji Achmad Siddiq Jember, 2025)
Low levels of early literacy skills among some lower-grade students, including those at MI Negeri 2 Jember, suggest that the implementation of beginning reading instruction has not yet achieved optimal outcomes. This condition is reflected in students’ difficulties in identifying letters, differentiating letter sounds, and reading syllables as well as simple words. The present study seeks to examine the types of early reading difficulties experienced by students and the factors contributing to these challenges. A descriptive qualitative approach was employed, utilizing classroom observations, diagnostic reading tests, and interviews as data collection techniques. The research participants consisted of several early-grade students identified as having difficulties in beginning reading skills. The findings indicate three dominant forms of difficulty, namely limited visual discrimination of letters, challenges in combining sounds into syllables or words, and low reading fluency. These difficulties are influenced by internal factors, such as students’ learning readiness and cognitive abilities, as well as external factors, including the limited variety of instructional methods used by teachers and insufficient literacy stimulation in the home environment. The results highlight the importance of implementing appropriate and focused interventions, such as structured phonics-based instruction, the use of visual learning media, and individualized learning assistance. Through these strategies, schools are expected to enhance early literacy development and improve the overall effectiveness of beginning reading instruction.